A REVIEW OF COMPARISON STUDIES IN APPLIED BEHAVIOR ANALYSIS. (13th March 2013) - Shabani, Daniel B.; Lam, Wing Yan
<x xml:space="preserve">Abstract</x> A commonly used research design in applied behavior analysis involves comparing two or more independent variables. Typically, the relative effectiveness of two different interventions is measured on a single dependent variable. In the current review, 54 comparison studies from seven different peer‐reviewed, behavior analytic journals were evaluated between the years 2002 and 2011. Each study was evaluated across seven dimensions: (1) experimental design, (2) setting, (3) participants, (4) type of comparison, (5) number of comparisons, (6) treatment integrity, and (7) outcome. There were some consistencies across studies, with half resulting in equivalent outcomes across comparisons. In addition, most studies employed the use of an alternating treatments or multi‐element single‐subject design and compared a teaching methodology. On the basis of these results, the value of comparison study as well as directions for future comparison research is discussed. Overall, comparison study is a worthy and important enterprise that requires a high degree of experimental control and a careful analyses of the results, regardless of whether the outcome clearly favored one independent variable or not. Copyright © 2013 John Wiley & Sons, Ltd.